Between the Lisbon Congress and the Brazilian Constituent assembly: Concepts of State of the Portuguese-gaucho entrepreneur Antônio José Gonçalves Chaves - Leme, Marisa Saenz [UNESP] (FapUNIFESP (SciELO), 2018)
This article assesses the concepts of Antônio José Gonçalves Chaves, a wealthy rancher from Portugal based in Rio Grande do Sul, about how would be the ideal state organization during a transitional phase between the United Kingdom statement - in which the Brazilian autonomy was contemplated in a liberal context - and the monarchy formation in a country that was almost independent, where the Constituent Assembly is being organized. There is a problematization on his positions, given the political context of that time, and considering his potential integration in what is called the liberal radical field, regarding the emphasis in the municipal and provincial issues, as well as the linking between his political and socioeconomic opinions. The primary source of the work is the book Memórias ecônomo-políticas sobre a adminis tração pública do Brasil, published by Chaves between 1822 and 1823, going through topics such as colonial administration, slavery, the land issue in Brazil and the socioeconomic structure of Rio Grande do Sul.
Entre o Congresso de Lisboa e a Constituinte Brasileira: Concepções de Estado do empresário luso-gaúcho Antônio José Gonçalves Chaves
Keywords: Federative monarchy; lLiberalism; Municipalities; Provinces